Programmed Death-Ligand 1 Protein and Colorectal Cancer Patient Survival Rates in Hasan Sadikin Hospital Bandung - Vandra Bina Riyanda; Reno Rudiman; Nurhayat Usman (HM Publisher, 2022)
Background: According to the American Cancer Society, Colorectal Cancer (CRC) is the third leading cause of cancer death in men and women in the United States. In Indonesia, CRC ranks as the third most common malignancy in both men and women. Programmed death-ligand 1(PD-L1) is a trans-membrane receptor ligand and negative regulatory signal for T cells that is elevated in several tumors including CRC and binds to programmed death 1 (PD-1) on T cells, B cells, dendritic cells and natural killer T cells. PD-L1 expression was found in tumor cells and tumor cells that infiltrate immune cells in several malignancies, including CRC. Methods: This study is a comparative analytic cross sectional study with consecutive sampling method. This study was conducted at Hasan Sadikin Hospital, Bandung from September to October 2021. Further statistical analysis was done SPSS version 25.0 for Windows (SPSS Inc., Chicago, Ill., USA). Results: The total sample in this study was 50 subjects with colorectal cancer patients at RSHS. The number of CRC patients who expressed PD-L1 were 23 (46%) and 27 subjects (54%). The majority of cancer patient survival 2 Years was 38 subjects (76.0%) and survivors of more than 2 years was 12 subjects (24.0%). Conclusion: There is no significant relationship between PD-L1 and survival rates in CRC patients.